Novel technologies open new frontiers in structural engineering. Issue 16 (December 2019) - Mufti, Aftab; Bakht, Baidar; Khalid, Huma
Civil infrastructures, being essential for modern and advanced societies, are the foundation of the dynamic economy and improvement of the quality of people's lives. The design and construction of such infrastructures involve a significant cost to a country, but the proper use of the scientific methods to monitor and maintain these structures can improve their cost-effectiveness. Civil engineers strive to design and construct structures meeting the highest standards of engineering in order to enhance the durability and functionality of such infrastructures. However, civil engineers have been rather slow in adopting civionics engineering to improve the useful life of infrastructures. It is noted that the new term 'civionics' was coined recently to denote structural health monitoring of civil structures with the help of electronic sensors. This article will discuss several lessons learned during the implementation of health monitoring systems for civil structures.